Taylor Series of Trigonometric Function for Lower Order Visualization - Shah, Yogendra Prasad (MATHunesa: Jurnal Ilmiah Matematika, 2024)
Abstract About the simplest kind of functions are polynomials. Under addition, multiplication, integration, and differentiation, they are closed. A function can be roughly expressed in terms of polynomials of a certain degree using Taylor series. This provides a clear picture of the function's local behavior. The Taylor series fits the function at the place where it is computed more closely the more terms there are. In various fields of natural and social science, trigonometric functions are used. In this work, we examine the tailored series of trigonometric functions using Wolfram Mathematica. The visualization of nature is also obtained using the same software, with point 0 and up to 5 order for sin, cos, sec, tan, cot, and cosec. Keywords:Polynomials, Taylor Sereis, Nautral and Social Science, Trigonometric function, Wolffram Methematica etc.